Non-contrast-enhanced magnetic resonance imaging: Objective figures in differentiation between acute and chronic deep venous thrombosis in the lower extremities. (December 2020) - Kao, Chih-Chen; Chen, Chien-Wei; Tseng, Yuan-Hsi; Tsai, Yuan-Hsiung; Wang, Shih-Chung; Huang, Yao-Kuang
Background: Deep vein thrombosis is a severe health problem. Treatment options may differ between acute and chronic deep vein thrombosis. Thus, distinguishing acute from chronic deep vein thrombosis is essential for patients with deep vein thrombosis. Triggered angiography non-contrast enhanced is an innovative magnetic resonance imaging protocol that may provide objective evidence in differentiating acute from chronic deep vein thrombosis. Method: We prospectively collected information on consecutive patients who had been evaluated through triggered angiography non-contrast enhanced magnetic resonance imaging for venous pathology in their lower extremities at a vascular wound care center in a tertiary hospital between April 2017 and January 2020. Patients included were divided into two groups with the onset time cutoff point of 21 days. All were undergone non-contrast-enhanced magnetic resonance imaging evaluation. Non-contrast-enhanced magnetic resonance imaging images were evaluated by a radiologist, and lower extremity venous thrombosis, collateral-vein development, and subcutaneous honeycombing were emphasized. Cohen's kappa coefficient was used to measure interrater agreement between the development of collateral veins, subcutaneous honeycombing, and symptom onset over 21 days. Results: Interrater agreement analysis revealed that the development of collateral veins was substantially correlated with the onset of symptoms over 21 days (Table 1). Additionally, the development of subcutaneous honeycombing detected through triggered angiography non-contrast enhanced magnetic resonance imaging also substantially agreed with the onset of symptoms over 21 days (Table 2). Conclusion: The diagnostic power of triggered angiography non-contrast enhanced magnetic resonance imaging in deep vein thrombosis is rival to current gold standard, color Doppler sonography. Triggered angiography non-contrast enhanced magnetic resonance imaging provides objective information on onset timing in patients with deep vein thrombosis that could differentiate acute from chronic deep vein thrombosis and provides guidance for treatment planning.